Toleransi dalam Bingkai Seni dan Budaya, Tradisi Pawai Ogoh-Ogoh sebagai Simbol Kerukunan Antar Umat Beragama di Kota Surabaya - Fatimah, Fatimah (Proceedings of Annual Conference for Muslim Scholars, 2024)
The ogoh-ogoh parade tradition is held every year in Surabaya to welcome the Nyepi Day of Hindus. All six religious communities participated in that celebration process. Uniquely, the ogoh-ogoh parade which is usually held at the temples, now has expanded on Surabaya center and become a source of harmony. This study aims to describe interfaith harmony and tolerance in Surabaya through the ogoh-ogoh parade tradition. This research used a qualitative method with anthropological approach and focused on tolerance education values. The techniques used are observation, interview, and documentation. The results of this study indicate that the form of harmony created is the participation of all six religious communities in Surabaya during the ogoh-ogoh parade. This year, the ogoh-ogoh parade coincided with Ramadhan for Muslims, so it became a moment to strengthen interfaith tolerance in Surabaya. The Hindus can perform their parade smoothly and Non-Hindus also feel entertained by that parade.